Accelerating the CBFM-enhanced jacobi method - Ludick, D.; Botha, M.; Maaskant, R.; Davidson, David (2017)
© 2017 IEEE. The Characteristic Basis Function Method (CBFM)-enhanced Jacobi method has been introduced as an improvement to the standard iterative Jacobi method for finite array analysis. This technique is a domain decomposition approach based on the Method of Moments (MoM) formulation. In some cases, e.g. array environments with a low degree of mutual coupling, the runtime benefit of the CBFM-enhanced Jacobi method is not as significant when compared to that of the Jacobi technique. The reason for this is that additional computational overhead is introduced during each iteration, i.e. setting up and solving the CBFM reduced matrix equation. In this work the adaptive cross approximation (ACA) algorithm is used to accelerate this step in the CBFM-enhanced Jacobi method.